PENGARUH PENERAPAN HUKUM UPAH MINIMUM REGIONAL PADA USAHA MIKRO, KECIL, DAN MENENGAH DI PALEMBANG - Andre Wiranata; Sri Handayani; Abdul Malik Sholeh Sholahuddin; Wijonarko (Lentera Ilmu Madani, 2026)
The implementation of the Regional Minimum Wage (UMR) is a policy established by the government as a form of legal protection for workers' rights to receive a decent wage. Workers and Micro, Small, and Medium Enterprises (MSMEs) have complained about asking for wage increases. In Palembang, there are a large number of MSMEs, ranging from selling pempek to songket crafts. In this study, we wanted to examine the impact of the UMR on MSMEs in Palembang by reading journals and news articles and analyzing eight sources from 2019 to 2025. The results show that the UMR this year is still considered sufficient for the needs of one person, even though the average employee already has a family. As a result, even being paid according to the UMR is still insufficient to meet the needs of a family. Moreover, MSMEs with limited capital are ultimately forced to pay below the standard. The impact on employees is very real, such as decreased work enthusiasm and decreased productivity, even many people are leaving work. There is a study from Lampung that uses a profit-sharing system (mudharabah) in MSME restaurants and shows positive results with an average above the UMR.